2017
DOI: 10.1016/j.pharmthera.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Maximising the potential of AKT inhibitors as anti-cancer treatments

Abstract: PI3K/AKT signalling is commonly disrupted in human cancers, with AKT being a central component of the pathway, influencing multiple processes that are directly involved in tumourigenesis. Targeting AKT is therefore a highly attractive anti-cancer strategy with multiple AKT inhibitors now in various stages of clinical development. In this review, we summarise the role and regulation of AKT signalling in normal cellular physiology. We highlight the mechanisms by which AKT signalling can be hyperactivated in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
195
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 163 publications
1
195
0
Order By: Relevance
“…The cases of skin rash and diarrhea were self-limiting and recovered once treatment stopped. These AEs have been noted in Phase 1 studies of other AKT inhibitors, such as the allosteric inhibitor MK2206 or kinase inhibitors such as GSK2141795 and ipatasertib (GDC-0068) (1,(12)(13)(14)(15)(16)(17). Hyperglycemia development was acute and indicative of the inhibitory effect of AZD5363 on AKT, a key regulator of glucose transport and metabolism in peripheral tissues and the liver (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cases of skin rash and diarrhea were self-limiting and recovered once treatment stopped. These AEs have been noted in Phase 1 studies of other AKT inhibitors, such as the allosteric inhibitor MK2206 or kinase inhibitors such as GSK2141795 and ipatasertib (GDC-0068) (1,(12)(13)(14)(15)(16)(17). Hyperglycemia development was acute and indicative of the inhibitory effect of AZD5363 on AKT, a key regulator of glucose transport and metabolism in peripheral tissues and the liver (17).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinically, sensitivity to AZD5363 has been strongly related to the presence of PIK3CA mutations (4,5), a trend that has also been observed with other inhibitors of the PI3K/AKT/mTOR pathway (6). PIK3CA mutations are found in breast and gynecologic cancers, and evaluation of AZD5363 in these settings is warranted (1).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A diversity of roles for AKT isoforms is emerging in different cancer types, and understanding these isoform-specific roles will be essential for optimal utilization of the AKT inhibitors already in clinical trials. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have clearly demonstrated that activation of the PI3K/AKT signaling pathway could regulate BIM expression (44,47). The PI3K/AKT signaling pathway triggers a cascade of cell responses, including cell cycle progression, programmed cell death and DNA damage repair in cancer (48). Furthermore, the PI3K/AKT signaling pathway is closely associated with the development and recurrence of cancer (49).…”
Section: Discussionmentioning
confidence: 99%